Ukraine and the East: Culturological Aspect - Pylypiuk, Oleh (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
Modern Oriental studies regard the East as the cradle of the world’s civilization, a web of unique cultural formations. Within the modern East–West paradigm, the research into the values of tradition should be underpinned by dominant axiological concepts in order to systematize contemporary ideas of the world, nature, the individual and mentality. In accordance with the central methodological principle of the research, archetypes are regarded as cultural universals. In the article, the typology of the cosmological and the spiritual elements (the Moon and the Word respectively) in the Oriental and Ukrainian traditions are highlighted, the emphasis being laid on the analysis of the semantic and thematic fields of the two archetypes